The Study of Inquiry Ability in the Photosynthesis Concept - Fatmawati, B.; Rustaman, N. Y. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The learning process has characteristics that reflect scientific, thematic, collaborative, and student-centered. This type of learning usually uses constructivist learning, and one of them is Inquiry. The inquiry is a process to get information by conducting observations or experiments to find answers or solve problems for questions or formulation a problem by using logical and critical thinking skills. This preliminary study focused on investigating new prospective teachersÃ¢â‚¬â„¢ inquiry ability. The respondents were new prospective teachers of Hamzanwadi University. The research instrument was a student worksheet with the topic Ã¢â‚¬Å“photosynthesis.Ã¢â‚¬Â Data analysis used descriptive statistical methods by calculating the score of each indicator of Inquiry after three assessments. Using of amount score to shows that for each indicator: (1) problem formulation (66), (2) Hypothesis (50), (3) Design (40), (4) Findings (12), and (5) Conclusions (10). It can be concluded that the new prospective teachersÃ¢â‚¬â„¢ in their involvement still needed to be trained, guidance, and continues to be developed. Therefore, Inquiry-based learning needs an extension for their next learning.